BE MORE FOCUSED TO REMAIN RELEVANT AND COMPETITIVE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 1 June 2015 – The direction and best practices for Universiti Sains Malaysia (USM) to remain competitive and relevant in the years ahead were discussed intensively, though in an easygoing manner with members of the University Board of Governors (LGU) here today.